Accidental Occupational Exposures among Dental Healthcare Workers in Asir Region, Saudi Arabia - Bokhari, K; Shariff, M; Wahab, MA; Togoo, RA; Hady, Yahya; Hassan, Yasser (Journal of Orofacial Research, 2012)
Aims and objectives: This study aims to assess the prevalence of accidental occupational injuries among dental healthcare workers in Asir region, Saudi Arabia, and thus the risk involved. Materials and methods: Self-administered questionnaires were distributed among dental specialists, general dental practitioners, dental interns, hygienists and dental assistants working in dental college (College of Dentistry, King Khalid University, Abha, KSA). Dentists working in private clinics and government hospitals in Asir Province, Saudi Arabia, were also included in this study. Results: Of the total 300 questionnaires, 190 were returned with a response rate of 63.3%. Of the respondents, 138 (72.63%) were males and the rest 52 (27.3%) were females. The response rate in this study was 63.3%. The total number of occupational injuries among DHCWs was 138 (72.5%) with a density rate of 0.72 per 100 persons per year which is significantly high. In the present study, a higher incidence of injuries occurred in the dental operatory and most of them being from needlestick injuries, i.e. 78 (56.2%). Conclusion: (1) Accidental occupational exposure incidence rate among DHCWs in Asir region, Saudi Arabia, is high as compared to other studies, (2) the majority of the injuries occurred in the dental operatory. Most of these injuries were caused by syringe needles and involved the finger or thumb.